K. E. Løgstrup’s philosophy of trust as the basis of moral education in the educational environment - Kulyk, Andrii (Filosofiya osvity. Philosophy of Education, 2025)
The article is dedicated to the exploration of the philosophy of trust by the Danish thinker and theologian Knud Ejler Løgstrup (1905–1981) as a foundation for moral education in the educational environment. The author emphasizes key concepts proposed by K. E. Løgstrup, such as the “ethical demand” and trust, which are considered not only as interpersonal phenomena but also as fundamental components of moral formation. Particular attention is given to the role of trust in the teacher-student relationship, which contributes to the development of moral consciousness, empathy, and responsibility. The article’s author emphasizes the relevance of the ideas of the Danish philosopher, who remains relatively unknown to Ukrainian readers, as well as their significance for contemporary Ukrainian pedagogy, particularly in the context of shaping a humanistic educational space where trust serves as a prerequisite for ethical education. The article also highlights the practical application of K. E. Løgstrup’s philosophical ideas in the educational process, specifically in fostering interdependence and moral responsibility among participants in the educational process. In this context, the philosophy of trust takes a central place, stressing the unconditional nature of the “ethical demand” and the necessity of assuming responsibility for the Other. The philosophy of trust in education plays a vital role in the development of life skills such as critical thinking, social interaction, and moral maturity. It fosters the creation of conditions for the conscious formation of individuals capable of navigating contemporary challenges and contributing to the construction of a just and sustainable society. Thus, the phenomenon of trust is not only a theoretical concept but also a practical tool for enhancing a unique educational existence in the modern world. Trust is a social reality that cannot be reduced merely to a phenomenon, as it emerges from human relationships and intertwines with our actions and daily lives.